Autoreduction of Copper on Silica and Iron‐Functionalized Silica Nanoparticles with Interparticle Mesoporosity. Issue 1 (20th November 2013) - Popova, Margarita; Ristić, Alenka; Mazaj, Matjaž; Maučec, Darja; Dimitrov, Momtchil; Tušar, Nataša Novak
Abstract Copper‐supported catalysts are of industrial importance in many catalytic processes. Mesoporous silica materials are of particular interest as green heterogeneous catalyst supports. In the present study we demonstrate the nature and reduction properties of copper oxide species, which are influenced by the peculiarity of the silica nanoparticles with interparticle mesoporosity (KIL family) and the presence of a second metal (iron) in the silica matrix. The copper‐containing KIL‐2 and FeKIL‐2 samples are prepared by incipient wetness impregnation. The reduction of copper oxide species is easier on the FeKIL‐2 supported sample in comparison to its KIL‐2 supported analogue, whereas the copper‐containing KIL‐2 sample shows higher catalytic activity in total toluene oxidation. The presence of iron in the FeKIL‐2 structure leads to autoreduction of copper followed by the redispersion and oxidation of metallic copper in the reaction medium; this results in the formation of different types of finely dispersed copper oxide species (<100 nm). The later species possess lower catalytic activity in toluene oxidation in comparison to species that are 100 nm in size and formed on KIL‐2.